Make a Match with Question Box Media for Improving the Thematic Learning Outcomes of Elementary School - Maruti, Endang Sri; Andriani, Wiwin; Irawan, Nico; Sari, Endah (Universitas Muhammadiyah Mataram, 2023)
Abstract: The purpose of this study was to improve thematic learning outcomes for class IV elementary school by using the Make a Match learning model assisted by the Question Box media. This type of research is Classroom Action Research (CAR) with 11 students as the research subject. The research (CAR) was carried out in two cycles, namely cycle I and cycle II. The procedure in this research is planning, implementation, observation, and reflection. Collecting data through interviews, observation, and test. Data analysis used qualitative data analysis, namely by collecting data, reducing data, presenting data, and drawing conclusions and quantitative analysis by analyzing data through test results, and measuring the percentage of completeness of test results. The results of the study after using the make a match model, the learning outcomes in the first cycle obtained an average of 73 with a percentage of 55% and in the second cycle an average of 92 with a percentage of 91%. The application of the make a match model to student learning outcomes has increased by 36%, so the results of the study indicate that the application of the make a match model assisted by the question box media can improve thematic learning outcomes at elementary school.